Streptococcus pyogenes and invasive central nervous system infection. (30th May 2018) - Randhawa, Ekamjeet; Woytanowski, John; Sibliss, Kedesha; Sheffer, Ian
Streptococcus pyogenes is a Gram-positive beta-hemolytic bacteria, also known as group A streptococci, that causes a range of infections. The most common presentation is acute pharyngitis; however, it is also implicated in skin and soft tissue infections, and less commonly bacteremia, osteomyelitis, pneumonia, otitis media and sinusitis. Group A streptococci infections of the central nervous system are exceedingly rare in the antibiotic era. The mechanism of infection is typically contiguous spread from existing infection or via direct inoculation. We present a case of an 81-year-old female with a past medical history of dementia, transient ischemic attacks, type 2 diabetes mellitus, hypertension, descending thoracic aortic aneurysm status post-stent placement in 2008, hepatitis C and hyperlipidemia who initially presented after being found unresponsive at home. Her initial symptoms were primarily of altered mentation and on evaluation was found to be in septic shock with suspicion of meningoencephalitis. Her initial workup included a computed tomography of head which was remarkable for left and right mastoid effusions. A lumbar puncture was performed with cloudy purulent fluid, an elevated white blood cell count, low glucose and elevated protein. The patient was initially started on broad spectrum coverage and soon had 4/4 blood cultures and cerebrospinal fluid cultures growing Streptococcus pyogenes . Empiric vancomycin, ceftriaxone and ampicillin were administered but switched to penicillin G in the setting of elevated total bilirubin and septic shock with multi-organ failure and narrowed to ampicillin–sulbactam based on sensitivities. Unfortunately, the patient deteriorated further due to septic shock and multi-organ failure and later died in the medical intensive care unit.